2015
DOI: 10.1111/nyas.12691
|View full text |Cite
|
Sign up to set email alerts
|

Moving with music for stroke rehabilitation: a sonification feasibility study

Abstract: Gross-motor impairments are common after stroke, but efficacious and motivating therapies for these impairments are scarce. We present a novel musical sonification therapy especially designed to retrain gross-motor functions. Four stroke patients were included in a clinical pre-post feasibility study and were trained with our sonification training. Patients' upper-extremity functions and their psychological states were assessed before and after training. The four patients were subdivided into two groups, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 28 publications
2
33
0
Order By: Relevance
“…[50][51][52] Furthermore, pairing movements with sounds using instruments (music playing) and sonification of movements have been recently shown to be possible candidates for improvement of motor deficits in acute and chronic patients. [20][21][22][23] Overall, these techniques rely on the establishment of fast auditory-motor mappings as well as auditory feedback processing during music performance (or movement sonification). These mechanisms seem to be responsible for the enhanced neural plasticity of premotor and motor regions encountered in stroke patients after music training.…”
Section: Discussionmentioning
confidence: 99%
“…[50][51][52] Furthermore, pairing movements with sounds using instruments (music playing) and sonification of movements have been recently shown to be possible candidates for improvement of motor deficits in acute and chronic patients. [20][21][22][23] Overall, these techniques rely on the establishment of fast auditory-motor mappings as well as auditory feedback processing during music performance (or movement sonification). These mechanisms seem to be responsible for the enhanced neural plasticity of premotor and motor regions encountered in stroke patients after music training.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] Strong influence of real-time auditory feedback on motor performance was thought to be due to its influence over the proprioceptive modality. [13][14][15][16] Hasegawa et al, 16 for instance, reported that training with auditory augmented biofeedback might facilitate the integration of auditory and proprioceptive systems. The authors suggested that the auditory system could promote a challenging, resource-dependent learning environment that might increase the reliance on proprioceptive doi: 10.1111/nyas.13967 information.…”
Section: Introductionmentioning
confidence: 99%
“…The third perspective is rehabilitation for recovery of impaired sensory-motor function after neurological or traumatic damage. Scholz et al [33] presents possible effectiveness of musical feedback for upper limb rehabilitation after stroke and discusses the advantage of it as inducing motivation of the patients as well as enhancement of sensory-motor learning with the help of the feedback. Playfulness is an important factor of rehabilitation, inducing motivation and active participation of the patients, to which a new technology can contribute [34].…”
Section: Discussionmentioning
confidence: 99%